Protective effect of Primula vulgaris against H2O2-induced DNA damage in fibroblast cells - Rezzan Aliyazicioglu (Frontiers in Genetics, 2015)
Oxidative stress comes out as a result of an imbalance between the reactive oxygen species (ROS) and antioxidant defenses. ROS besides damaging cellular molecules such as proteins and lipids, can also cause the formation of strand breaks and pyrimidine- and purine-derived lesions in DNA, thus leading to genome destabilization. To protect biomolecules against the attack of free radicals and/or to prevent the damage from happening, numerous natural and synthetic free radical scavengers and antioxidants have been developed and studied. Primula is a plant genius which comprises about 400 species. It is accepted as a good antioxidant source due to its phenolic contents. The aim of this study was to evaluate the protective effects of the water extract of Primula vulgaris on fibroblast cells exposed to oxidative agents by comet assay. Fibroblast cells (passage number is between 1 and 6) were pre-treated for 1 h with different concentrations (100, 250, and 500 µg/mL) of water extracts Primula vulgaris before the genotoxic agent. Then, the cells were treated with 20 µM H2O2 at 5 minutes and comet assay was performed. The water extracts of Primula vulgaris significantly decreased H2O2-induced DNA damage at the concentrations of 250 and 500 µg/mL (P<0.0001). In conclusion, Primula vulgaris extract demonstrated antigenotoxic activity by protecting cells against oxidative DNA damage.